Bone Cement Augmentation for Cervical Vertebrae‐Ossification of the Posterior Longitudinal Ligament Complex Contributes to Anterior Controllable Antedisplacement and Fusion in Patients With Osteoporosis - Lu, Qilin; Li, Xugui; Zhang, Bin; Shi, Jiangang; Sun, Jingchuan (Orthopaedic surgery, 2025)
Anterior controllable antedisplacement and fusion (ACAF) is an effective strategy in treating cervical ossification of the posterior longitudinal ligament (C-OPLL). The controllable antedisplacement of the vertebrae-OPLL complex (VOC) through screws is both the most critical and technically challenging procedure, especially in osteoporosis (OP) condition. This study aims to introduce a modified method to significantly improve the procedure of VOC antedisplacement in ACAF. The modified ACAF was used to treat 22 patients both with C-OPLL and OP from January 2020 to January 2023. The cohort comprised 17 females and 5 males, with an age of 60.68 ± 1.2 years (50-71 years). During this modified ACAF, bone cement was injected into the VOC, and the corresponding steps of grooving were improved. Japanese Orthopedic Association (JOA) score, complications, and fusion conditions were documented. A paired t-test was used to compare the changes before and after surgery. Twenty-two C-OPLL patients were successfully treated by the modified ACAF. The operation time was 270.5 ± 14.8 min, and the intraoperative blood loss volume was 303.6 ± 13.0 mL. All patients were followed up for 26.55 months on average. The JOA score with 12.18 ± 1.68 at the last follow-up was significantly improved (vs. 8.59 ± 1.89 of presurgery, p < 0.05). No cement leakage was found during the augmentation, and 0.4 mL of bone cement was injected in each VOC, which obviously enhanced screws anchorage. All VOCs were successfully hoisted after the augmentation without screw loosening. Twenty-two C-OPLL patients achieved satisfactory fusion at the last visit. Bone cement augmentation with modified steps of grooving can effectively assist the VOC antedisplacement in ACAF for OP group and has potential instantaneous revision ability for the intraoperative screw loosening for no-OP group.